Publicity Stunt: The Importance of Seymour Rogers and Free Water in the Creation and Survival of Liberal, Kansas, 1885-1888 - Dowell, Nathan (Kansas State University, The Chapman Center for Rural Studies, 2017)
A study connecting the story of where the name of Liberal, Kansas came from to the factors that impacted town survival in Seward County during the late 1880’s and early 1890’s. Seymour Rogers, the figure who is credited with inspiring the name of “Liberal,” is explored within the context of a county vying for trade, railroads, the county seat, business, and, perhaps most importantly, attention. This study uses land deeds related to Rogers’ time in Seward County, past and present newspapers from Liberal, personal accounts of settlers in early Seward County, Kansas Historical Markers located in Seward County, and various historical reference works on Seward County, southwestern Kansas, and the state.
Nathan Dowell, “Publicity Stunt: The Importance of Seymour Rogers and Free Water in the Creation and Survival of Liberal, Kansas, 1885-1888,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/249.
Keywords: Arkalon; cattle industry; Liberal Post Office; Rock Island Railroad; Seward County; western expansion